2008
DOI: 10.1089/vbz.2007.0185
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Involvement in Childhood Brucellosis: A Case Report

Abstract: Brucellosis is primarily a zoonotic disease that continues to be an important public health problem. It is a rare, multisystem infection of childhood and it may present with a wide spectrum of clinical presentations and complications. However, lung involvement is extremely rare in the course of childhood brucellosis. This case report describes a 6-year-old child who was referred to our hospital as meningococcemia but diagnosed as lobar pneumonia in follow-up. Brucella agglutination test and bone marrow culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…In the present case, thoracentesis was not performed because the pleural effusion was minimal. According to some authors, the efficacy of blood cultures decreases significantly with the previous use of antibiotics and with subacute and chronic forms of infection (2,6). Negative blood cultures in the present case may be related to the use of antibiotics before the investigation for brucellosis.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…In the present case, thoracentesis was not performed because the pleural effusion was minimal. According to some authors, the efficacy of blood cultures decreases significantly with the previous use of antibiotics and with subacute and chronic forms of infection (2,6). Negative blood cultures in the present case may be related to the use of antibiotics before the investigation for brucellosis.…”
Section: Discussionmentioning
confidence: 55%
“…Due to its high degree of morbidity, both for animals and humans, it is a significant cause of economic loss and represents a serious public health problem in many developing countries (2). Inhalation of contaminated aerosols is a route by which Brucella can make direct contact with the respiratory system and, according to some authors, it is a route that has potential for use in biological warfare (6). Because of wide distribution of the microorganism through the bloodstream to various organs, including the lungs, bacteremic spread may be the most probable route for acquiring pulmonary brucellosis (2,4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 effusion, granulomas, solitary nodules, and hilar and paratracheal lymphadenopathies. [15][16][17] Gur and associates, 6 Lubani and associates, 14 and Hatipoglu and associates 15 found that lung involvement of brucellosis was 5%, 0.6%, and 10%.…”
Section: Discussionmentioning
confidence: 98%